Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kinerja Guru (Analisis Supervisi Kepala TK Al-Himmah Muara Tebo) - Ahmad Ridwan; Nur Aina; Khairul Anwar; Hairunnisah; Dewi Suryani (STAI Auliaurrasyidin Tembilahan, 2023)
Academic supervision of the principal is an activity of coaching, observing, and assessing teacher performance in the teaching and learning process. This study aims to determine the academic supervision activities carried out by the principal of Al-Himmah Muara Tebo Kindergarten (TK) in improving the quality of teaching teachers. This research uses a qualitative approach involving the principal and 3 teachers. Data were collected through observation and interviews. The data were analyzed descriptively, that is, data reduction, data presentation, and conclusion drawing. The results showed that supervision has been carried out one to two times a year, and has been met the regulations. It improves the quality of teacher competencies, performance, and skills – which is seen in terms of learning processes and outcomes.